Low Rate of Microbiologic Relapse in Two-Stage Exchange for Hip Prosthetic Joint Infections. (4th October 2017) - Henry, Michael; Russell, Celeste; Nocon, Allina; Westrich, Geoffrey; Brause, Barry; Miller, Andy
Abstract: Background: Prosthetic joint infection (PJI) is a grave complication of total hip arthroplasty (THA). Historically, two-stage arthroplasty exchange has been considered to be the definitive approach to eradicating infection and preserving joint function. However, patients are increasingly presenting with higher rates of comorbidities traditionally associated with poorer orthopedic surgical outcome, including advanced age, obesity and diabetes. We investigated whether two-stage exchange remains effective for THR PJI at an orthopedic specialty hospital, and what were the microbiologic etiologies in repeat infections. Methods: A retrospective cohort of THA PJI treated with two-stage exchange was identified by query of hospital coding records from 2009 to 2014. The primary endpoint was defined as 2-year implant retention without further surgery. Failure was defined as a recurrence within in 2 years. Microbiologic failure was defined as a recurrence of the previously treated organism. Descriptive statistics were completed using the Fisher's exact test for categorical variables and the Mann–Whitney U -test for continuous variables. Results: One hundred and forty-four patients meeting Musculoskeletal Infection Society International Consensus criteria for THA PJI were identified. The average age was 65 years and 60% were female. One hundred and twenty-seven (88.2%) were cured at 2 years. Pathogens included Staphylococcus aureus (MSSA, 23%; MRSA, 13%), coagulase-negative staphylococci (17%), and streptococci (17%). In univariate analysis, no links were noted between primary outcome and patient age, comorbidities (including diabetes and tobacco), BMI, microbiology, or symptom duration. Of the 17 patients who did not meet criteria for success, 11 (65%) were diagnosed with new, microbiologically distinct infection. The remaining six met our criteria for microbiologic failure; four of the six patients had S. aureus infection (three MSSA). Conclusion: We present 2-year outcomes on a large cohort of THA PJI treated with two-stage exchange arthroplasty. Nearly, two-thirds of the patients who failed were found to have a new infection at the time of relapse. Only 4% of the patients in our cohort failed to achieve cure of the primary infection. Two-stage exchange continues to be an effective approach to PJI treatment with a low rate of microbiologic failure. Disclosures: All authors: No reported disclosures.